2004
DOI: 10.1083/jcb.200401141
|View full text |Cite
|
Sign up to set email alerts
|

AMSH is an endosome-associated ubiquitin isopeptidase

Abstract: The JAMM (JAB1/MPN/Mov34 metalloenzyme) motif has been proposed to provide the active site for isopeptidase activity associated with the Rpn11/POH1 subunit of the 19S-proteasome and the Csn5-subunit of the signalosome. We have looked for similar activity in associated molecule with the SH3 domain of STAM (AMSH), a JAMM domain–containing protein that associates with the SH3-domain of STAM, a protein, which regulates receptor sorting at the endosome. We demonstrate isopeptidase activity against K48-linked tetrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
373
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(406 citation statements)
references
References 33 publications
25
373
2
6
Order By: Relevance
“…To clarify the intracellular localization of AMSH, we transfected HeLa cells with a CHMP3 expression vector and analyzed the localization of the exogenous CHMP3 as well as the endogenous AMSH by confocal microscopy. In accordance with previous findings (Itoh et al, 2001;McCullough et al, 2004), we detected AMSH as scattered puncta throughout the cytoplasm with moderate expression in the nucleus ( Fig. 2A).…”
Section: Amsh Associates With the Escrt-iii Protein Chmp3supporting
confidence: 93%
See 2 more Smart Citations
“…To clarify the intracellular localization of AMSH, we transfected HeLa cells with a CHMP3 expression vector and analyzed the localization of the exogenous CHMP3 as well as the endogenous AMSH by confocal microscopy. In accordance with previous findings (Itoh et al, 2001;McCullough et al, 2004), we detected AMSH as scattered puncta throughout the cytoplasm with moderate expression in the nucleus ( Fig. 2A).…”
Section: Amsh Associates With the Escrt-iii Protein Chmp3supporting
confidence: 93%
“…In studies aimed at finding molecules associated with STAM, we identified the AMSH deubiquitinating (DUB) enzyme (Tanaka et al, 1999;McCullough et al, 2004). AMSH possesses an isopeptidase domain characterized by the JAB1/MPN/Mov34 metalloenzyme (JAMM) domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, some OTU family components such as OTUB1 and A20 hydrolyze Lys48-linked chains, whereas TRABID and OTUD5 have preference for Lys63 linkages (Virdee et al, 2010). Furthermore, Cezanne preferentially cleaves Lys11 over Lys48 and Lys63 linkages (Bremm et al, 2010), whereas JAMMs share the specificity for Lys63-linked polyubiquitin (McCullough et al, 2004;Sato et al, 2008;Cooper et al, 2009). Finally, the Josephin ATXN3-editing activity shows a restricted specificity for K63-linked chains (Winborn et al, 2008).…”
Section: Enzymatic Roles and Regulation Of Dubsmentioning
confidence: 99%
“…USP8 has an important role in the stabilization of RTKs through deubiquitylation, allowing their recycling to the plasma membrane (Niendorf et al, 2007), although other studies have suggested that USP8 might promote degradation of RTKs (Alwan and van Leeuwen, 2007). In addition, the endosomeassociated AMSH (also known as STAMBP) promotes EGFR recycling at the expense of lysosomal sorting (McCullough et al, 2004;Clague and Urbe, 2006). USP18 has been identified in a recent RNA interference screen as a new regulator of EGFR synthesis by modulating its translation (Duex and Sorkin, 2009).…”
Section: Signaling Pathwaysmentioning
confidence: 99%